Подходы к решению задачи составления расписаний учебных занятий в образовательных учреждениях - Щерба, В.В.; Ячменев, Е.Ф. (Культура народов Причерноморья, 2014)
Предложены критерии по решению задач составления расписания, которые формируют
условия необходимого и достаточного по наличию ресурсов. Формализация задачи составления
расписания требует от нас наличия критериев оценки программного обеспечения. Достоинства и
недостатки существующего программного обеспечения позволило сформулировать общие требования к
решению таких задач. За результатами проведеного аналізу існуючих підходів виробок-тана єдина концепція
складання розкладу в навчальних закладах. Запропоновано критерії щодо вирішення завдань складання
розкладу, які формують умови необхідного і достатнього за наявності ресурсів. Формалізація задачі
складання розкладу вимагає від нас наявності критеріїв оцінки програмного забезпечення. Переваги та
недоліки існуючого програмного забезпечення дозволило сформувати загальні вимоги до вирішення таких
завдань. Based on the analysis of existing approaches vyrabo-tang single concept of scheduling in schools.
The criteria for solving scheduling problems, Koto-rye create the conditions necessary and sufficient for the
presence of re-resources. Formalization of the scheduling problem requires us to-differences evaluation criteria
of the software. Dignity and non-sufficiency of existing software allowed sformu-plated general requirements for
the solution of such problems. Comparative analyses implemented software allowed them to formulate such
criteria for use: the number of licensed Rabo jobs is; the cost of connecting additional workplace; client-server
architecture; software platform; work through the Web-based interface; technical support; open source
software; -possibility of creating their own limitations; intellectual support of the scheduling process; online
backups audit-ries; scheduling of examinations; publication schedules on the portal; the operational adjustment
of schedules; Reporting in the various sections.